Improvement of Learning Outcomes Using the Scramble Model with Interactive Video Media - Khoirul Anam; Ridho Surya Kusuma; Suharti Sirajuddin; Eric Santosa (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2026)
The integration of active learning strategies with digital media has become increasingly essential in higher education to enhance student learning outcomes. This classroom action research investigated the effectiveness of the Scramble learning model supported by interactive video media in improving student achievement in the English Language Education Department at Universitas Negeri Makassar. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection. A total of 32 undergraduate students participated, selected through purposive sampling. Data collection employed tests, observations, and reflective notes, while data analysis combined descriptive statistics with normalized gain (N-gain) to evaluate improvements in learning outcomes. The findings showed consistent progress across cycles. Average student performance improved significantly from the baseline measurement to the second cycle, demonstrating that the instructional strategy effectively supported knowledge acquisition. Moreover, the integration of Scramble activities with interactive video fostered greater classroom engagement, collaboration, and motivation. Students responded positively to the use of multimedia-based tasks, which provided a more dynamic and student-centered learning environment. The study concludes that the Scramble model, when combined with interactive video media, is a highly effective approach to improving learning outcomes in teacher education courses. Beyond raising academic achievement, this model also contributes to enhancing students’ critical thinking, active participation, and collaborative learning. These findings highlight the potential of technology-enhanced active learning models to address challenges in higher education and provide meaningful benefits for both teaching practice and student development.